AC impedance spectroscopy characteristics of chloride-exposed cement pastes. (10th February 2020) - Hu, Xiang; Shi, Caijun; Yuan, Qian; de Schutter, Geert
Highlights: The microstructure and interfacial properties of cement paste are studied. The modifications of electrical parameters due to chloride penetration are studied. The properties of EDL are discussed by the obtained capacitance. The calculated EDL thickness is correlated to the chloride concentration in EDL. Abstract: In this paper, the characteristics of AC impedance spectroscopy of cement paste immersed in chloride solution were measured and analyzed with a proposed equivalent circuit model. The elements in the proposed equivalent circuit, including the resistance of interface between electrode and specimens, resistance of continuous and discontinuous pore, capacitance of solid phase and electrical double layer (EDL) were discussed. The results showed that the resistance of interface between electrode and testing specimen was much lower than that of cement paste. With the increase of chloride concentration in the soaking solution, the resistance of continuous gradually decreased due to the higher conductivity of chloride solution. Stripped out the impacts of concentration of pore solution on resistance of pores, the resistance of continuous pore increased firstly due to the decrease of continuous pore volume from the formation of Friedel's salt. However, the resistance of discontinuous pores gradually decreased with the increase of soaking solution concentration due to the transformation of continuous pores to discontinuous pores. The reaction between chloride ions and hydration products and formation of Friedel's salt decreased the porosity of cement pastes and led to higher capacitance of solid phase. Based on an idealized two-plate capacitor model for EDL, the thickness of EDL was calculated from the measured capacitance. The decrease of EDL thickness with chloride concentration in soaking solution was in agreement with the results of chloride contents in EDL obtained from pore solution expression test.